Progranulin directly binds to the CRD2 and CRD3 of TNFR extracellular domains. Issue 21 (23rd September 2013) - Jian, Jinlong; Zhao, Shuai; Tian, Qingyun; Gonzalez-Gugel, Elena; Mundra, Jyoti Joshi; Uddin, Sardar MZ; Liu, Ben; Richbourgh, Brendon; Brunetti, Ryan; Liu, Chuan-ju
Abstract : We previously reported that PGRN directly bound to TNF receptors (TNFR) in vitro and in chondrocytes (Tang, et al., Science, 2011). Here we report that PGRN also associated with TNFR in splenocytes, and inhibited the binding of TNFα to immune cells. Proper folding of PGRN is essential for its binding to TNFR, as DTT treatment abolished its binding to TNFR. In contrast, the binding of PGRN to Sortilin was enhanced by DTT. Protein interaction assays with mutants of the TNFR extracellular domain demonstrated that CRD2 and CRD3 of TNFR are important for the interaction with PGRN, similar to the binding to TNFα. Taken together, these findings provide the molecular basis underlying PGRN/TNFR interaction and PGRN‐mediated anti‐inflammatory activity in various autoimmune diseases and conditions.